Fundamentals of MALDI-ToF-MS Analysis Applications in Bio-diagnosis, Tissue Engineering and Drug Delivery - Hosseini, Samira; Martinez-Chapa, Sergio O. (SpringerBriefs in Forensic and Medical Bioinformatics,, 2017)
This book presents the fundamentals and applications of Matrix Assisted Laser Desorption/Ionization Time-of-Flight Mass Spectrometry (MALDI-ToF-MS) technique. It highlights the basic principles, the history of invention as well as the mechanism of ionization and mass determination using this technique. It describes the fundamental principles and methods for MALDI spectra interpretation and determination of exact chemical structures from experimental data. This book guides the reader through the interpretation of MALDI data where complex macromolecular spectra are simplified in order to present the major principles behind data interpretation. In addition, each chapter describes how MALDI-ToF-MS analysis provides necessary understanding of the copolymer systems that have been designed for specialized biomedical applications.